Behind the food labels - Wiseman, Peter; Russell, Geoff (Australian food technology ;, 1993)
Made in conjunction with the Australian Government Analytical Laboratories (AGAL), this progam looks at food testing and subsequent labelling in Australia. The first half of the program deals with the work of AGAL in Adelaide, where chemists demonstrate the analysis of a sample of corn chips to determine fat, protein and carbohydrate content, the most commonly displayed nutrients on food labels in Australia. The second half of the program explores the problem of interpreting the labels, improving nutritional literacy, Recommended Dietary Intakes and a summary of a healthy diet.